2020
DOI: 10.1038/s41398-020-01034-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between UBE3A and SNORD116 expression and features of autism in chromosome 15 imprinting disorders

Abstract: Chromosome 15 (C15) imprinting disorders including Prader–Willi (PWS), Angelman (AS) and chromosome 15 duplication (Dup15q) syndromes are severe neurodevelopmental disorders caused by abnormal expression of genes from the 15q11–q13 region, associated with abnormal DNA methylation and/or copy number changes. This study compared changes in mRNA levels of UBE3A and SNORD116 located within the 15q11–q13 region between these disorders and their subtypes and related these to the clinical phenotypes. The study cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…We hypothesize that overexpression of UBE3A may contribute to the decreased performance capacities in adults with an mUPD. This is supported by a study of Baker et al who showed that higher UBE3A mRNA levels were associated with lower PIQ scores [ 62 ]. However, the maternally imprinted genes may also play a role.…”
Section: Discussionsupporting
confidence: 67%
“…We hypothesize that overexpression of UBE3A may contribute to the decreased performance capacities in adults with an mUPD. This is supported by a study of Baker et al who showed that higher UBE3A mRNA levels were associated with lower PIQ scores [ 62 ]. However, the maternally imprinted genes may also play a role.…”
Section: Discussionsupporting
confidence: 67%
“…Second: Does a differential abundance of SNORD115s in AD plasma EV reflect an impaired metabolic or regulatory pathway with a role in AD pathogenesis? In brain, SNORD116 and SNORD115 clusters have been primarily associated with Prader-Willi syndrome (PWS) (Bortolin- Cavaille and Cavaille, 2012;Cassidy et al, 2012;Chamberlain, 2013;Cavaillé, 2017;Deogharia and Majumder, 2018;Baker et al, 2020;Chung et al, 2020). In the majority of PWS cases, there is a deletion of the entire SNURF-SNRPN locus on the paternal human chromosome 15q11-q13 where SNORD115 is mapped (Nicholls et al, 1993;Cavaillé, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this diagnostic screening study, participants for the test validation cohort were recruited as part of the FREE FX study 3 , 16 and through pathology and clinical genetics services between January 2000 and December 2016 as detailed in eAppendix 1 in the Supplement . Data collection included retrospectively retrieved newborn blood spots (NBS) and dried blood spots (DBS) made at time of recruitment, as well as venous blood, buccal epithelial cells, and saliva samples for individuals with PWS (109 samples), AS (48 samples), or Dup15q (9 samples) and controls (1190 samples) from the general population.…”
Section: Methodsmentioning
confidence: 99%
“…In this diagnostic screening study, participants for the test validation cohort were recruited as part of the FREE FX study 3,16 and through pathology and clinical genetics services between January 2000…”
Section: Participants and Ethicsmentioning
confidence: 99%